Effects of particle composition on thorium scavenging in the North Atlantic. (15th July 2018) - Lerner, Paul; Marchal, Olivier; Lam, Phoebe J.; Solow, Andrew
Abstract: The dependence of thorium scavenging by particles on particle composition is examined at selected stations of the U.S. GEOTRACES North Atlantic Section (GA03). Scavenging is here described by the apparent, first-order rate constant of Th adsorption onto particles ( k 1 ), as estimated from an inversion of Th radioisotope and radioactive parent data. Our k 1 estimates are regressed against particle phase data using two different models. Model I considers biogenic particles (POC + PIC + bSi), lithogenic particles, Mn (oxyhydr)oxides, and Fe (oxyhydr)oxides as regressors, and k 1 as the regressand. Model II considers ln(POC + PIC + bSi), ln(lithogenic particles), ln(Mn (oxyhydr)oxides), and ln(Fe (oxyhydr)oxides) as regressors, and ln( k 1 ) as the regressand, where ln() denotes the natural logarithm. Thus, models I and II posit that the effects of particle phases on k 1 are, respectively, additive and multiplicative. These models are applied to three groups of stations: (i) all selected stations, (ii) stations west of the Mauritanian upwelling region ("western stations"), and (iii) stations within that region ("eastern stations"). We find that model II appears to better describe the effect of particle composition on k 1 than model I. Particle composition explains a larger fraction of the variance of k 1 for the eastern stations ( R 2 = 0.60 for model I and 0.67 for model II) than for the western stations ( R 2 = 0.26 for model I and 0.39 for model II). When considering all stations, the variance of k 1 explained by particle composition is intermediate ( R 2 = 0.50 for model I and 0.51 for model II). According to model II, the variance of k 1 explained by particle composition is predominantly due to biogenic particles at the eastern stations and to Mn (oxyhydr)oxides at the western stations. Additionally, we find that particle composition does not explain a significantly different proportion of variance of k 1 than particle concentration. It is thus concluded that, at our selected stations, (i) biogenic particles and Mn (oxyhydr)oxides more strongly influence Th scavenging than any other phases considered and (ii) particle composition and particle concentration have comparable effects on this process.